2021
DOI: 10.1038/s41598-021-04147-1
|View full text |Cite
|
Sign up to set email alerts
|

A global analysis of conservative and non-conservative mutations in SARS-CoV-2 detected in the first year of the COVID-19 world-wide diffusion

Abstract: The ability of SARS-CoV-2 to rapidly mutate represents a remarkable complicancy. Quantitative evaluations of the effects that these mutations have on the virus structure/function is of great relevance and the availability of a large number of SARS-CoV-2 sequences since the early phases of the pandemic represents a unique opportunity to follow the adaptation of the virus to humans. Here, we evaluated the SARS-CoV-2 amino acid mutations and their progression by analyzing publicly available viral genomes at three… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 26 publications
1
3
0
Order By: Relevance
“…2B ), suggesting that newly arising variants (e.g., Q, M, and R) have a low genetic barrier toward the codon change at this position. This is in agreement with a prior global mutational analysis study of SARS-CoV-2, which demonstrated that SNAMs are present at much higher frequencies ( 29 ). However, some exceptions on the basis of selection pressure exist, for instance, certain L452 mutations despite having a lower genetic barrier (e.g., P and V) showed very low global frequency ( Fig.…”
Section: Resultssupporting
confidence: 92%
“…2B ), suggesting that newly arising variants (e.g., Q, M, and R) have a low genetic barrier toward the codon change at this position. This is in agreement with a prior global mutational analysis study of SARS-CoV-2, which demonstrated that SNAMs are present at much higher frequencies ( 29 ). However, some exceptions on the basis of selection pressure exist, for instance, certain L452 mutations despite having a lower genetic barrier (e.g., P and V) showed very low global frequency ( Fig.…”
Section: Resultssupporting
confidence: 92%
“…The most mutation is D614G, namely 16 samples. This mutation is classi ed as a non-conservative type of amino acid change because it has a PAM value of 11, as well as different properties and characteristics (Table 5) (Balasco et al 2021).…”
Section: Resultsmentioning
confidence: 99%
“…Speech recognition systems represent a trend that became more entrenched during the COVID-19 pandemic (Balasco et al. 2021 ; Mumtaz et al. 2021 ).…”
Section: Securitymentioning
confidence: 99%